2011
DOI: 10.1038/onc.2011.368
|View full text |Cite|
|
Sign up to set email alerts
|

FOXO3a represses VEGF expression through FOXM1-dependent and -independent mechanisms in breast cancer

Abstract: Vascular endothelial growth factor (VEGF) plays a central role in breast cancer development and progression, but the mechanisms that control its expression are poorly understood. Breast cancer tissue microarrays revealed an inverse correlation between the Forkhead transcription factor FOXO3a and VEGF expression. Using the lapatinib-sensitive breast cancer cell lines BT474 and SKBR3 as model systems, we tested the possibility that VEGF expression is negatively regulated by FOXO3a. Lapatinib treatment of BT474 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
129
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(144 citation statements)
references
References 57 publications
14
129
1
Order By: Relevance
“…In addition, our current study found FOXO3a, which suppresses VEGF-A expression (Karadedou, et al, 2012), experienced a subtle nuclear to cytoplasmic shift. This would predictably reduce FOXO3a nuclear activity and facilitate VEGF-A expression.…”
Section: Discussionsupporting
confidence: 48%
“…In addition, our current study found FOXO3a, which suppresses VEGF-A expression (Karadedou, et al, 2012), experienced a subtle nuclear to cytoplasmic shift. This would predictably reduce FOXO3a nuclear activity and facilitate VEGF-A expression.…”
Section: Discussionsupporting
confidence: 48%
“…Indeed, our data indicate that VEGF expression are RAS -dependent in multiple systems. Furthermore, FOXO3a regulates VEGF production through FOXM1 (48). Because hypoxia increases the activity of PARPi and the combination of a PARPi and cedirainib (a VEGFR inhibitor) is highly active in patients (49), the effect of MEKi and PARPi on vascularity could contribute to activity of the combination in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature have documented the tumour suppressor function of FOXO3a in breast cancer. For instance, Karadedou et al demonstrated that nuclear FOXO3a expression induced by lapatinib had a central role in the suppression of breast cancer progression and metastasis by negatively regulating VEGF expression 23. However, this study only involved the HER2-amplified breast cancer cell lines as model systems and was lacking clinical data.…”
Section: Discussionmentioning
confidence: 97%